Pengembangan Kapasitas (Capacity Building) Kepala Madrasah Dalam Meningkatkan Mutu Pendidikan - Erwin Indrioko; Ulfa Rhomaisha Basar (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
One of important challenges about facing educational organizations in the advancement of technology and information is how to manage a quality on an ongoing basis. In the context of education, the notion of including encryption of inputs, processes, outputs, and outcomes of education. In order to create an educational system that has a diversity way to realize the purpose of education can be achieved by renewing the madrasah mission and strategy as well as implementing it. All of these are subject to the discovery of capacity building in all areas of good governance as well as sustainable. Capacity building should be implemented effectively and continuously on three levels, namely: 1) Individual level, for example: personal skills and requirements, knowledge, behavior, grouping of work and motivation of people's work in organizations. 2) The institutional level or the whole unity, for example: organizational structures, decision-making processes within organizations, procedures and work mechanisms, arrangements and infrastructure, links to organizations. 3) System levels, such as work-related regulators, basic policy and policies that support the achievement of a certain policy objectivity.